Performance Analysis of an Atkinson Cycle Engine under Effective Power and Effective Power Density Conditions - Gonca, G. (POLISH ACAD SCIENCES INST PHYSICS, 2017)
This study presents performance optimization of an Atkinson cycle engine using criteria named as effective power and effective power density conditions. The effects of design and operating parameters such as compression ratio, cycle pressure ratio, cycle temperature ratio, equivalence ratio, bore/stroke ratio, inlet temperature, inlet pressure, engine speed, friction coefficient, mean piston speed and stroke length, on the performance characteristics have been examined. Moreover, the energy losses have been determined as fuel energy and they have been classified as incomplete combustion losses, friction losses, heat transfer losses, and exhaust output losses. Realistic values of specific heats have been used depending on temperature of working fluid. The results of the study can be assessed as an engineering tool by the Atkinson cycle engine designers.
Keywords: VARIABLE SPECIFIC-HEATS; IRREVERSIBLE MILLER CYCLE; INJECTED DIESEL-ENGINE; AIR-FUEL RATIO; MAXIMUM POWER; THERMODYNAMIC PERFORMANCE; FRICTION; DESIGN; OPTIMIZATION; PARAMETERS; Physics